AYAT-AYAT BIAS GENDER DALAM SURAT ANNISA’: KAJIAN SEMANTIK - Muhandis Azzuhri (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2015)
there’s no such language that free from gender bias. Arabic language as Islamic religion holy book’s language has createdgender bias in all utilizing fiil (verb) and isim (noun), especially sura at an-Nisa’. gender bias verse at sura an-Nisa’ analyzed with semantictheory namely interpreting all character, word, and sentence that related with gender bias, chronologically and historically so we obtainunderstanding contextual meaning, not textual meaning. therefore, gender bias meaning at sura an-Nisa’ is not focused only on biologicalmeaning, namely only mudzakar (masculine) or muannats (feminine) but alsorelated with language’s soscial culture aspect that developedby its speaker community.